The influence of growth and maturation on stretch-shortening cycle function in youth - Radnor, J. M.; Oliver, J. L.; Waugh, C. M.; Myer, G. D.; Moore, I. S.; Lloyd, R. S. (Sports Medicine, 2018)
Hopping, skipping, jumping and sprinting are common tasks in both active play and competitive sports. These movements utilise the stretch-shortening cycle (SSC), which is considered a naturally occurring muscle action for most forms of human locomotion. This muscle action results in more efficient movements and helps optimise relative force generated per motor unit recruited. Innate SSC development throughout childhood and adolescence enables children to increase power (jump higher and sprint faster) as they mature. Despite these improvements in physical performance, the underpinning mechanisms of SSC development during maturational years remain unclear. To the best of our knowledge, a comprehensive review of the potential structural and neuromuscular adaptations that underpin the SSC muscle action does not exist in the literature. Considering the importance of the SSC in human movement, it is imperative to understand how neural and structural adaptations throughout growth and maturation can influence this key muscle action. By understanding the factors that underpin functional SSC development, practitioners and clinicians will possess a better understanding of normal development processes, which will help differentiate between training-induced adaptations and those changes that occur naturally due to growth and maturation. Therefore, the focus of this article is to identify the potential underpinning mechanisms that drive development of SSC muscle action and to examine how SSC function is influenced by growth and maturation.